THE PARTICIPATION OF WOMEN, YOUNG PEOPLE AND CHILDREN IN THE MANAGEMENT OF FISHING RESOURCES IN THE MIDDLE SOLIMÕES REGION: ACCESS TO INCOME AND RESILIENCE FROM ARTISANAL FISHING - Costa, Edgar Augusto de Medeiros; Alencar, Edna Ferreira (Cordis: Revista Eletrônica de História Social da Cidade, 2025)
The present study aims to address the participation of women, young people and children in fisheries resource management projects. Through a bibliographical review and analysis of the content of interviews, we were able to understand the benefits of managed fishing programs for women and young people in communities who now have access to a stable and permanent income, which allows them to earn a living in fishing crafts, a viable and profitable activity. In addition to the financial aspect, managed fishing projects ensure that future generations have contact with practices related to artisanal fishing, enabling the circulation of traditional knowledge of these communities. The participation of women is fundamental in this process, as it ensures the inclusion of young people and children, whose contributions renew and improve the knowledge accumulated by fishing communities over time.